Study on Widening Equipment Limit in Horizontal Curve Section of Suspension Monorail Traffic - Xiao WU; Jian WANG; Yinguang XU; Chunbo WANG (机车电传动)
Suspension monorail traffic is mainly suitable for special areas with narrow roads or high building density. Usually these areas have more curve sections. The equipment limit of curve section directly affects the feasibility of the project, the investment of the project and the safety of driving. There is a big difference between suspended monorail transit system and traditional rail transit system. At present, there is no relevant criterion and standard for direct use at home and abroad. For this reason, taking H-BAHN suspended monorail vehicle in Germany as an example, through the analysis and study of vehicle structure, the factors and calculation formulas of widening equipment boundary in horizontal curve section were analyzed, and the relevant formulas were used to calculate the widening of equipment boundary.